Analysis of ‘’Blue Economy’’ Contents in Junior High School Social Science Book - Shahibah Yuliani; Enok Maryani; Siti Nurbayani; Disman Disman (STKIP Taman Siswa Bima, 2023)
The utilization of marine and coastal natural resources is becoming increasingly important to support economic growth in Indonesia, one of which is the blue economy. The blue economy does not only need to be known by the general public, especially fishermen, but can be learned early on by junior high school students. In addition, the blue economy is important for students to learn because it has the benefit of increasing environmental awareness and global issues. This study aims to describe the results of the analysis of blue economy content in social science book for grade 7. The method used in this study is literature review. The results of the study show that in grade 7 textbooks, there is content on the potential for natural resources of fishing communities. However, there has been no in-depth discussion of this blue economy, so that another supporting book is needed in fulfilling this material.